Comparative Effectiveness of Calcimimetic Agents for Secondary Hyperparathyroidism in Adults: A Systematic Review and Network Meta-analysis - Palmer, Suetonia C.; Mavridis, Dimitris; Johnson, David W.; Tonelli, Marcello; Ruospo, Marinella; Strippoli, Giovanni F.M. (American journal of kidney diseases, 2020)
Comparative benefits and harms of calcimimetic agents used for the treatment of secondary hyperparathyroidism have not been well characterized. We sought to compare the effectiveness of 3 calcimimetic agents using published data. Systematic review of randomized controlled trials and network meta-analysis. Adults with chronic kidney disease enrolled in a clinical trial of a calcimetic agent. MEDLINE, EMBASE, CENTRAL (from February 7, 2013, to November 21, 2019), and a published meta-analysis. Two reviewers independently extracted the study data, assessed risk of bias, and rated evidence certainty using Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria. Frequentist network meta-analysis was conducted. The primary review outcomes were achievement of a target reduction in serum parathyroid hormone (PTH) levels and hypocalcemia. Additional outcomes were nausea, vomiting, serious adverse events, all-cause mortality, cardiovascular mortality, heart failure, and fracture. 36 trials (11,247 participants) were included. All except 4 trials involved dialysis patients. Median follow-up was 26 weeks (range, 1 week to 21.2 months). Compared with placebo, calcimimetic agents had higher odds of achieving target PTH levels with high or moderate certainty. Etelcalcetide had the highest odds of achieving a PTH target compared with evocalcet (OR, 4.93; 95% CI, 1.33-18.2) and cinacalcet (OR, 2.78; 95% CI, 1.19-6.67). Etelcalcetide appeared to cause more hypocalcemia than cinacalcet and evocalcet. Cinacalcet and to a lesser extent etelcalcetide appeared to cause more nausea than placebo. Differences in risk for mortality, cardiovascular end points, or fractures across calcimimetic agents could not be discerned with sufficient certainty. Lack of longer-term data; heterogeneous end point definitions. Evidence of the benefits of calcimimetic therapy is limited to short-term assessment of a putative surrogate outcome (serum PTH). Although etelcalcetide was associated with the largest reduction in PTH levels, side-effect profiles differed across the 3 calcimimetic agents, making it not possible to identify 1 preferred agent.